Elaboração de soda italiana a partir de xaropes artesanais de pitaya branca (Hylocereus undatus) e uva (vitis vinifera) separadamente, com açucar colorido. - MANCILIA, Ana Laura Teles; FERNANDES, Ana Luiza Souza; PINTO, Diego Roberto Freire; OLIVEIRA, Kamilly Eduarda Correa de (075, 2024)
This study presented gelatin as a polypeptide derived from collagen, with the main commercial sources being the skin and bones of cattle and pigs. The importance of seeking alternatives, such as carrots, a vegetable with significant production, was highlighted, considering the annual demand for gelatin, estimated at 200,000 metric tons, mainly for use in desserts. The objective of the work was to develop a concentrated carrot gelatin and evaluate its sensory characteristics with the participation of untrained evaluators. The methodology included the review of scientific articles published between 2000 and 2021 and the development of the project at Etec Padre José Nunes Dias, located in Monte Aprazível. The gelatin was produced from cooked and raw carrots, subjected to a process of extraction of the concentrate, dilution and mixing with unflavored gelatin and sugar, until reaching the desired consistency. The sensory analysis was performed with untrained evaluators and was evaluated by taste, smell, aroma and color. The Gelatin that the public rated best was the raw one.

This study presented gelatin as a polypeptide derived from collagen, with the main commercial sources being the skin and bones of cattle and pigs. The importance of seeking alternatives, such as carrots, a vegetable with significant production, was highlighted, considering the annual demand for gelatin, estimated at 200,000 metric tons, mainly for use in desserts. The objective of the work was to develop a concentrated carrot gelatin and evaluate its sensory characteristics with the participation of untrained evaluators. The methodology included the review of scientific articles published between 2000 and 2021 and the development of the project at Etec Padre José Nunes Dias, located in Monte Aprazível. The gelatin was produced from cooked and raw carrots, subjected to a process of extraction of the concentrate, dilution and mixing with unflavored gelatin and sugar, until reaching the desired consistency. The sensory analysis was performed with untrained evaluators and was evaluated by taste, smell, aroma and color. The Gelatin that the public rated best was the raw one.
Keywords: Uva; Produtos naturais; Recursos Naturais